Джерела до життєпису І. Сошенка - Амеліна, Л. (Студії мистецтвознавчі, 2007)
The article presents two archival documents from the fund of the Ukrainian National Art Museum. They deal with the biography of Ukrainian artist Ivan Soshenko. One of the documents is a certificate of his death. He died on July 18, 1876 in the town of Korsun. The cause of death was a carbuncle (infectious skin disease followed by blood poisoning). The second one is a receipt in name of artist’s father Maxim Soshenko. The receipt was issued on May 28, 1817 and it contains information that artist’s father paid money tax to count Branytsky.